2016
DOI: 10.5562/cca2996
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Protective Mechanism of Iron(II)-polyphenol Binding with OH-related Molecular Descriptors

Abstract: Abstract:The linear models for the calculation of pIC50, pKa1 and Epa for 12 polyphenolic compounds (catechins, flavonols, catechol and gallol derivatives) were developed. As descriptors we used the number of vicinal (Nv) and non-vicinal (Nnv) OH groups, as well as the number of OH vicinal pairs as possible Fe 2+ chelate sites (Nch). The models gave r ˃ 0.9 and standard errors of 0.13, 0.26 and 0.04 for pIC50, pKa1 and Epa, respectively. For modelling of pIC50, Nch is better variable than Nv, and vice versa fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The new model we have developed for the estimation of oxidation potentials of flavonoids based on the number of OH groups is simpler than our previous models (29)(30)(31) and yielded better statistics than the models reported in references 29 and 30. In addition, the model has turned out to be very stable, even though the inter-laboratory differences between experimental potentials were high (up to 0.096 V).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The new model we have developed for the estimation of oxidation potentials of flavonoids based on the number of OH groups is simpler than our previous models (29)(30)(31) and yielded better statistics than the models reported in references 29 and 30. In addition, the model has turned out to be very stable, even though the inter-laboratory differences between experimental potentials were high (up to 0.096 V).…”
Section: Resultsmentioning
confidence: 82%
“…We reported similar correlations and proposed models for the estimation of E p1 based on OH-related descriptors (29)(30)(31).…”
mentioning
confidence: 71%
“…Flavonoids, with their multiple hydroxyl groups and the carbonyl group on ring C (flavones), have several available sites for metal complexation. Miličević et al noticed a strong correlation between polyphenols’ antioxidative activity and their affinity for Fe(II) ions (represented by binding constants), suggesting that the suppression of Fenton reaction is most probably caused by chelation of the ion [ 39 ]. Porfírio et al found that Fe(II) complex of morin, quercetin and fisetin (most probably 1:1) displayed higher antioxidant capacity for Ce(IV) (about 15%, 32% and 28%, respectively) than flavonoids alone [ 42 ].…”
Section: Chelating Properties Of Flavonoidsmentioning
confidence: 99%
“…Generally, we can say that flavonoid’s ability for ROS suppression, if we do not consider their effect on enzyme activity, is based mainly on their chelation of Fe(II) ions, optionally preceded by reduction of Fe(III) ions [ 39 , 71 , 72 ]. This effect is influenced by other factors such as pH and polarity of the reaction milieu [ 80 , 81 ].…”
Section: Chelating Properties Of Flavonoidsmentioning
confidence: 99%
See 1 more Smart Citation